Theoretical Analysis of the Countercurrent Gas-Solid Heat Transfer During the Drying of Brown Coal Briquettes with Circulating Gas - Sharpin P. C (The Australasian Institute of Mining and Metallurgy, 1966)
The countercurrent gas-solid heat transfer during the drying of brown coal briquettes in the pilot carbonization plant at Morwell has been analysed and theoretical gas and solid temperature distributions through the drier have been calculated. Although the calculations rest on several simplifying assumptions, the theoretical temperature distributions compare well with those observed in practical operation. Valuable conclusions are reached as to the effects of changes in drier operating conditions on the rate of drying of the briquettes which controls the strength of the char produced. The analysis shows why a limitation was reached in the improvement of char strength in the pilot plant in 1961 due to the performance of the drier and a prediction is made of a way in which the limitation could be overcome.